Viewpoint – Rent-Seeking in Agricultural Water Management: An Intentionally Neglected Core Dimension? - Walter Huppert (Water Alternatives, 2013)
In the early and mid-1980s, two seminal papers on agricultural water management came as a shock to the international professional community. They drew attention to the fact that public irrigation is particularly prone to rent-seeking and corruption. Both papers – one by Robert Wade in 1982 and the other by Robert Repetto in 1986 – described hidden interests of the involved stakeholders in irrigation development and management that open doors to opportunistic behaviour – thus perpetuating technical and economical inefficiencies. About twenty-five years later, Transparency International (TI) in its often cited Global Corruption Report 2008 – dedicated to the issue of corruption in the water sector – made the following statement: "corruption remains one of the least analysed and recognised problems in the water sector. This report provides a first step in filling this gap" (TI, 2008: 106). The question arises as to why, through twenty-five years following the publications of Wade and Repetto, the topics of corruption and rent-seeking in agricultural water management seldom gained serious attention in international research and development. And why, strangely enough, the critical topic of rent-seeking is hardly dealt with in the above-mentioned report and even in recent publications of the Water Integrity Network (WIN). The author, drawing on thirty-five years of experience in the field of agricultural water management and on cases from research and from development cooperation, puts forward his personal viewpoint on this matter. He contends that local as well as international professionals on different levels in the water sector are caught in multifaceted conflicts between formal objectives and hidden interests – and often tend to resort to rent-seeking behaviour themselves.